HYPERTROPHIC OBSTRUCTIVE CARDIOMYOPATHY IN AN 8-MONTH OLD FEMALE INFANT SUSPECTED INFANTILE ONSET POMPE DISEASE - Purnami, Made Dwi; Gunawijaya, Eka (Medicina; Vol 45 No 2 (2014): Mei 2014, 2015)
Hypertrophic cardiomyopathy (HCM) is an autosomal dominant cardiac disorder marked with muscular hypertrophy of the left ventricle, associated obstruction of left ventricular outflow. About 0.2% of all cases worldwide. The majority of patients are asymptomatic, and some present with severe activity- limiting symptoms. The diagnosis of HCM before the age of 2 years is rare and usually discovered by chance, during the investigation of a murmur. Progressive disease characterized by prominent cardiomegaly, cadiomyopathy, hepatomegaly, musle weakness or hypotonia, respiratory distress, feeding difficulties and failure to thrive as presenting sign and symptoms are often referred to infantile Pompe disease. A deficiency of of the enzyme acid alpha glucosidase disease, result in lysosomal accumulation of glycogen in heart and skeletal muscle. Cardiorespiratory failure is the cause of significant morbidity and mortality in the first year of life. We reported a rare case, 8 month-old female with frequent respiratory distress since 2 months before admission. Physical examination showed dyspnea with chest wall retraction, no cyanosis, with grade III systolic murmur at midclavicular line sinistra, ICS IV- V and floopy infant. Chest films showed   pneumonia and cardiomegaly. The echocardiogram demonstrated bi-ventricular and interventricular hypertrophy with left ventricular obstruction. Laboratory finding there was increased levels of glutamic oxaloacetic acid transferase, alanin aminotransferase, and lactate dehydrogenase. Patient was diagnosed with hypertrophic obstructive cardiomyopathy of suspected infantile onset pompe disease. Despite medical treatment with propanolol dan diuretics, there was no significant improvement and she was died after 26th days of treatment in intermediate ward. [MEDICIN A 2014;45:108-14]
Keywords: hypertrophic obstructive cardiomyopathy, infant